Self-Leadership dan Penyesuaian Akademik Mahasiswa Baru - Yapono, Farid (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. New students often encountered obstacles, especially adapted to the academic environment. For being well adjusted students need the ability of self-leadership. Based on that reason, this research aims to test a correlation between self-leadership and academic adjustment in college students in the first year. Subjects of the study were 93 freshman classes at the some public universities located in Surabaya. Data were collected by questionare and Likert scale. Further, the data were analyzed by the Pearson product moment correlation. Results showed positively correlation between self-leadership and students’ academic adjustment at the first year. Keywords: self-leadership, students’ academic adjustment